1984
DOI: 10.1111/j.1526-4610.1984.hed2404211.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Efficacy of Biofeedback in Headache

Abstract: SYNOPSIS This paper presents a retrospective study of 84 headache patients seen in the Behavioural Medicine Unit of Sunnybrook Medical Centre, of whom 53 were treated with biofeedback. Of the 84 patients assessed, half were tension headache and half were migraine. Both groups were treated in one of three ways: 1. Frontal EMG FB only. 2. Hand skin temperature (HST) only. 3. EMG FB followed by HST FB. Assessment results showed the migraine group to have longer headache histories and more severe headaches than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Fahrion 6 found that ability to reach a high temperature of 95.5 degrees F was predictive of success. Billings et al 8 determined that a formula utilizing (1) points given for each phase that temperature is maintained above baseline, multiplied by (2) points given for having an ending temperature higher than the session beginning temperature, yielded a score which correlated significantly with headache improvement. Werbach and Sandweiss 6 found that the best predictor of headache outcome was the inability to handwarm during the first session of TBF-W + AT.…”
Section: Studymentioning
confidence: 99%
“…Fahrion 6 found that ability to reach a high temperature of 95.5 degrees F was predictive of success. Billings et al 8 determined that a formula utilizing (1) points given for each phase that temperature is maintained above baseline, multiplied by (2) points given for having an ending temperature higher than the session beginning temperature, yielded a score which correlated significantly with headache improvement. Werbach and Sandweiss 6 found that the best predictor of headache outcome was the inability to handwarm during the first session of TBF-W + AT.…”
Section: Studymentioning
confidence: 99%
“…Preliminary investigations of the utility of thermal biofeedback with adults have suggested that it may be an effective method of treating tension headaches 24,25 . However, the efficacy of thermal biofeedback has not been investigated with children suffering from tension headaches.…”
mentioning
confidence: 99%
“…16 Comparison of the first five minutes of the session with the last five minutes shows an average decrease in muscle tension of 1.4 microvolts and an average decrease in HST of 0.05 F. Fifteen of the 25 patients decreased their muscle tension over the session while only 10 showed an increase in hand skin temperature. The mean EMG and HST levels at the monitoring session were 19.60 (sd=10.60) and 86.84 (sd=6.40), respectively.…”
Section: Pre-test Data -Cognitive Measuresmentioning
confidence: 93%
“…Once the sensors were attached, 16 the patients sat in a semi-reclining chair in a dimly lit room. Subjects first completed the questionnaires.…”
Section: Subjectsmentioning
confidence: 99%